Agriculture Through Ages: Modern Challenges Towards Biofuels and Bioenergy Crops Agriculture (Tanzania Journal for Population studies and Development, 2010)
Human civilization has been through culminations of great achievements. This paper explores agricultural development in ancient and modern times, and the challenges yet to be resolved. At the beginning man invented how to cultivate, how to make fire, and moved from wild lifestyle to more settled livelihoods. He learnt and practised extensive systems such as slash-and-burn cultivation for millennia, and as population increased and knowledge accumulated he developed intensive systems such as greenhouse agriculture. Great developments have been associated with the industrial revolution of the 17th, 18th and 19th centuries, especially in areas of mechanization and use of industrial agricultural inputs. Both agricultural practices and industrial production have cost the world greatly in terms of environment degradation and environmental pollution. While the world is looking for remedies to environment degradation and pollution that are now intolerably threatening climate change, a new agricultural economic opportunity has emerged, which is not only important because of economic necessity, but it is also an important option towards solving the global warming and climate change threats. This is the use of biofuels and bioenergy as alternatives to fossil fuels use as a source of energy and power. The urgency of bio-fuels agriculture, particularly, seems to overwhelm what is the basic ecological role of world food subsistence agricultural production, with an additional role of producing almost the same food products to satisfy also the bio-fuels industry. This will obviously conflict on land use choices and commodity priority, and needs very thorough effort in planning and appropriate use of resources to avoid probably un-manageable consequences in near future.